Venöse Thrombembolien bei Tumorpatienten - Pabinger, I.; Alt-Epping, B.; Demarmels Biasutti, F.; Langer, F.; Wörmann, B.; Riess, H. (Hämostaseologie, 2011)
Venous thrombembolism (VTE) is one of the most frequent complication in cancer patients. The current options in prophylaxis and therapy have to be balanced against the risks of major bleeding and the burden for the patients. The Gesellschaft für Thrombose- und Hämostaseforschung, the Deutsche Gesellschaft für Palliativmedizin and the German speaking Societies of Hematology and Oncology have recently published guidelines on VTE in cancer patients. Recommendations include diagnostics, individual prophylaxis and treatment.
Keywords: Cancer; tumour; venous thrombosis; pulmonary embolism; venous thromboembolism